From inhaler to lung: clinical implications of the formulations of ciclesonide and other inhaled corticosteroids - Nave, Ruediger (Dove Medical Press, 2013)
Asthma continues to be a global health problem and currently available treatments such as corticosteroids can cause unwanted side effects. Inhaled corticosteroids (ICS) are recommended as first-line therapy for reducing airway inflammation and have a distinct advantage over oral preparations as they provide a direct route of delivery to the lungs. However, local deposition of ICS in the oropharynx can lead to oral candidiasis, dysphonia, and pharyngitis. The pharmaceutical quality is a primary concern of any ICS asthma treatment, with a higher quality product resulting in improved efficacy and safety profiles. The particle size distribution and the spray force velocity of an ICS may directly influence lung deposition, and the spray duration of a device is another important factor when coordinating inhalation. Recent advances in ICS device and formulation technology have resulted in significant improvements in the efficacy of available asthma treatments. In particular, hydrofluoroalkane (HFA) solution technology and the development of smaller particle sizes have resulted in the production of new ICS formulations that have the ability to directly target drug delivery to the site of airway inflammation. Both the ICS formulation and the pressurized metered-dose inhaler device used to administer ciclesonide (CIC) HFA have been developed to treat the underlying chronic inflammation associated with asthma. CIC is administered as a prodrug which is activated in the lungs, leading to minimal oropharyngeal deposition. The small particle size of CIC results in the delivery of a high fraction of respirable particles to the small airways of the lungs, resulting in high lung deposition and continual dose consistency. This review summarizes how CIC administered as an HFA formulation is an effective treatment for asthma.